BIMBINGAN DAN KONSELING BERBASIS TADABBUR SIRAH UNTUK MENGEMBANGKAN SPRITUALITAS SISWA DI MADRASAH - M. Amirullah; Edil Wijaya Nur; Aswar Aswar (Media Bina Ilmiah, 2023)
The study of spirituality in the context of guidance and counseling shows an increasing graph of progress. The late 1990s and early 2000s were the year when the issue of spirituality in the context of counseling and psychology was increasingly being discussed by various associations such as the American Counseling Association (ACA), the Association for Spiritual, Ethical, and Religious Values in Counseling (ASERVIC) American Psychology Association (APA), and The Council for Accreditation of Counseling and Related Educational Program (CACREP). This paper aims to describe an idea of the application of guidance and counseling based on tadabur sirah in madrasah (Islamic School) to improve aspects of spirituality for students. Tadabur sirah is an effort to contemplate the contents of the Quran in depth as an effort to improve the spirituality. Various research results show that spirituality can give a positive influence in improving the quality of human life. One way that can be done to improve the spirituality is by learning and contemplating the historical stories that exist in the Qur'an through storytelling techniques. Various research results also show that storytelling techniques have been proven to be effective in teaching and transferring the noble values contained in the stories.